Evaluation of the results of laboratory and instrumental investigations in endocrinology - Сиволап, Віктор Денисович; Каджарян, Віталій Георгійович; Бідзіля, Петро Петрович; Солов'юк, Олександр Олегович; Syvolap, V. D.; Kadjaryan, V. G.; Bidzilya, P. P. (My University, 2016)
In the textbook is a material on the evaluation of the results of laboratory and instrumental researches at the most widespread diseases of the endocrine system. The need for training allowances due to changes in the program of the discipline "Internal medicine", approved by MH of Ukraine in 2015
Keywords: internal diseases; endocrinology